Condition of mangrove in the waters of Pangkil Village, Teluk Bintan District, Bintan Regency - Mario Putra Suhana; Edo Edo; Susiana Susiana; Rochmady Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Pangkil Village is one of the areas located on the coast of Bintan Island, Teluk Bintan District. This island has an aquatic ecosystem with abundant marine resources, one of which is the mangrove ecosystem. Mangroves are the main supporting ecosystem for life activities in coastal areas that play an important role in maintaining the balance of environmental biological cycles. This study aims to determine the condition, distribution and density level of mangroves in the waters of Pangkil Village. This research was conducted in February-March 2021. The research method is purposive sampling, which means that the research station points are chosen intentionally based on the consideration of the condition of the existence of mangroves or the density of mangroves. The research station points were determined as many as 8 stations, at each station consisting of transects and at each transect consisting of 3 sample plot plots (Transect Line Plot). The density level data was collected using a line transect measuring 10x102 which was drawn from the sea to the land and the distribution of mangroves using lansat-8 imagery. The level of mangrove density in the waters of Pangkil Village is still quite good. The results of the research on the level of mangrove density in the waters of Pangkil Village are classified as good with the distribution of mangrove areas in the waters of Pangkil Village covering an area of 40.23 ha, with an average density level of 1,033 ind/ha per station to 1,733 ind/ha. with medium and solid status based on the Decree of the Minister of the Environment No. 201 year 2004.